2002
DOI: 10.1146/annurev.cellbio.18.012502.083438
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Pollination and Fertilization in Plants

Abstract: In flowering plants, pollen grains germinate to form pollen tubes that transport male gametes (sperm cells) to the egg cell in the embryo sac during sexual reproduction. Pollen tube biology is complex, presenting parallels with axon guidance and moving cell systems in animals. Pollen tube cells elongate on an active extracellular matrix in the style, ultimately guided by stylar and embryo sac signals. A well-documented recognition system occurs between pollen grains and the stigma in sporophytic self-incompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
235
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(236 citation statements)
references
References 106 publications
0
235
0
1
Order By: Relevance
“…Selfing can ensure reproductive success where mates are limited (by low densities or pollen movement) (Baker, 1955); however, it can lead to reduced genetic variation and offspring fitness. Outcrossing can be achieved by a complex array of mechanisms reducing self-pollination and self-fertilisation (Barrett, 1998;Lord and Russell, 2002;Hiscock and McInnis, 2003;Takayama and Isogai, 2005). Self-pollination can be limited by pre-pollination mechanisms, such as temporal and spatial separation of male and female structures, and pollinator behaviour (Barrett, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selfing can ensure reproductive success where mates are limited (by low densities or pollen movement) (Baker, 1955); however, it can lead to reduced genetic variation and offspring fitness. Outcrossing can be achieved by a complex array of mechanisms reducing self-pollination and self-fertilisation (Barrett, 1998;Lord and Russell, 2002;Hiscock and McInnis, 2003;Takayama and Isogai, 2005). Self-pollination can be limited by pre-pollination mechanisms, such as temporal and spatial separation of male and female structures, and pollinator behaviour (Barrett, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Self-pollination can be limited by pre-pollination mechanisms, such as temporal and spatial separation of male and female structures, and pollinator behaviour (Barrett, 1998). Selfincompatibility may act at various stages: blocking germination on the stigma, growth through the style, and penetration and fertilisation of the ovary (Lord and Russell, 2002;Takayama and Isogai, 2005). Neotropical trees are predominantly outcrossing, despite earlier predictions that selfing would dominate due to low tree densities in wet forests (Baker, 1959;Bawa et al, 1985;Ward et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in our understanding of guidance mechanisms for the pollen tube and the transcriptional activity of the gametes [2][3][4], our knowledge on the actual mechanism of fertilization remains extremely limited. A remarkable recent study has shown, however, that the fusion between the sperm cells and the female gametes involves the conserved protein GENERATIVE CELL SPECIFIC 1 (GCS1) [5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pollen tubes grow at extremely high rates in vivo and consequently have a very high demand for energy (Lord, 2000;Lord and Russell, 2002). Because pollen is often in excess, tubes must compete for access to ovules; thus, rapid growth is key to male reproductive success .…”
mentioning
confidence: 99%
“…Because pollen is often in excess, tubes must compete for access to ovules; thus, rapid growth is key to male reproductive success . The pollen tube is known to interact intimately with the nutrient-rich extracellular matrix of the stylar tract and adhesion factors implicated in pollen tube growth have been identified in lily (Lilium longiflorum) and tobacco (Nicotiana tabacum; Lord, 2000Lord, , 2003Lord and Russell, 2002). Pollen tube growth and guidance are separable genetically , but the identities of diffusible signals directing pollen tubes to the ovules and ultimately permitting entry to the micropyle have remained elusive until recently (Johnson and Preuss, 2002;Higashiyama et al, 2003;McCormick and Yang, 2005).…”
mentioning
confidence: 99%